3D-data Runstenar i Hälsingland 3D data Runestones in Hälsingland - Kitzler Åhfeldt, Laila; Zedig, Henrik (Swedish National Heritage Board, 2025)
3D-scans of all preserved runestones in Hälsingland. This dataset includes 3D-models of 11th century runestones 3D-scanned for documentation and analysis at Runverket (the runic research group) at the Swedish National Heritage Board.

The signum Hs + number is an ID-code used in the record of runic inscriptions kept by Runverket at the Swedish National Heritage Board. The signum is used in most publications and web-based resources. It is the key to find further references on a specific runic inscription and the object carrying it.

The 3D-scanning was made by Henrik Zedig, Länsstyrelsen Västra Götaland, with a handheld laser scanner HandySCAN BLACK ELITE (blue laser) from Creaform with a resolution of 0.40 mm. The data is here provided as STL-files.

Noice has been reduced by using the function Thin in Zeiss INSPECT Optical 3D at a threshold level of 0.02-0.03 mm.

Due to its size, the runestone Hs 10 is divided into six sections.

The runestone Hs 14 is scanned twice, first in the round and secondly focussing on the runic inscription using a higher resolution.
Keywords: Runor; Runsten; Runinskrift; Runes; Runestone; Rune stone; Runic inscription; Hälsingland; Viking Age; 1000-tal; 11th century; 3D-skanning; 3D-scan; 3D models; Runverket; Hs 1; Hs 2; Hs 3; Hs 4; Hs 6; Hs 9; Hs 10; Hs 11; Hs 12; Hs 14; Hs 15; Hs 16; Hs 21; Archaeology; Arkeologi; History and Archaeology; Historia och arkeologi